A Comparison Analysis Between Pre-departure and Transitioned Expat-Preneurs - Kumpikaitė-Valiūnienė, Vilmantė; Duobienė, Jurga; Mihi-Ramirez, Antonio (Frontiers in Psychology, 2021)
This paper contributes to the understanding on the reasons that lead to entrepreneurship in other countries. We focus on expat-preneurs, those who decided to undertake business opportunities in other countries (before or after settling there). Using comparison analysis and logistic regression, we examine pre-departure and transitioned expat-preneurs’ demographic characteristics and push-pull factors that lead them to expatriate. From a survey conducted in 2015-2016 of 5,532 Lithuanians expatriated in 24 countries, a sample of 308 respondents with their own businesses abroad was selected. This research contributes to the literature on expat-preneurs, with empirical evidence on pre-departure and transitioned self-initiated (SI) expat-preneurs. The results revealed that demographic features matter when studying such global entrepreneurs. It is a process experienced differently by males and females and, as such, it can be considered as gender selective. Thus, more pre-departure expat-preneurs are male than female, but there is a growing number of female transitioned expat-preneurs. Pre-departure expat-preneurs are older and less educated than transitioned ones and have been pushed to move abroad by issues such as political corruption or a non-supportive tax system, and are attracted by a higher possibility of self-realisation as well as the prestige of the host country. Meanwhile, transitioned expat-preneurs have been pushed to emigrate due to family reasons or too few employment opportunities in their home country.